Role of Consumer Satisfaction as a Mediating of Effect Halal Labels, Brand Image, and Price on Purchasing Decisions - Abelmar, Ryan Farhan; Mansur, Amin; Karimullah, Karimullah; Zhafiraah, Nazma Riska (Research of Islamic Economics, 2024)
Consumers make judgments about what to buy by looking for, offering, assessing, and spending money on goods and services that they believe will meet their requirements. Purchasing decisions are to buy the brand they like from various available alternatives. Currently, business competition is very tight, especially in companies that produce products. Price perception is very important. The purpose of this study is to determine how price, brand perception, and halal labelling affect consumers' decisions to buy. consumer satisfaction as a mediating factor of Wardah cosmetic products. Research is designed as explanatory research. The study population was people who wore and had used cosmetics from Wardah, with 100 responders serving as the sample. The Partial Least Squared Structural Equation Modeling Method was used to gather data. The findings demonstrated that factors that mediated consumer pleasure in purchasing decisions were not halal labeling, brand image, or price. Purchase decisions are positively and significantly impacted by consumer satisfaction. Purchaser satisfaction can be a mediator that influences pricing for purchasing decisions, but kosher labels and brand image are not significant. Managerial implications of marketing and branding strategies such as halal label management, brand image development, and pricing strategies such as competitive pricing.